Effect of Sheet Pile Driving on Geotechnical Behavior of Adjacent Building in Sand: Numerical Study - Ali Basha; Mohammed Elsiragy (Salehan Institute of Higher Education, 2019)
Construction vibration such as sheet pile driving can produce earthborn vibrations which may be leads to problems for the supporting soils and adjacent structures. Vibrations create the stress waves traveling outward from the source through the soil and cause structural damage due to dynamic vibration induced settlement. The main aim of the present research is to study the vibration effect through sheet pile driving technique on the surrounding soil and adjacent structure. A series of plain strain finite element analysis using Plaxis 8.2 dynamic module is run to simulate the installation technique of a sheet pile unit using driving technique (hammer type). The effect of construction stages with different embedded sheet pile depth, sand relative density, and foundation distance from the driving source is also studied. The influence of hammer driving amplitude on the foundation response and excess pore water pressure are presented. The results showed that the increase of both embedment sheet pile depth and hammer efficiency can significantly produce higher excess pore water pressure and foundation settlement. The increase of sand density can also has a great effect in increasing the foundation damage of adjacent structure compared with low sand relative density. The building damage can significantly take place when the driving is closed to foundation.